AKTUALISASI PENDAMPINGAN (COACHING) BERBASIS MODEL GROW DALAM MENINGKATKAN KREATIVITAS GURU RUMPUN PAI DI MADRASAH IBTIDAIYAH - Ngalimatul Mukarromah; Ahmad Ali Riyadi; Diana Nur Sholihah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This article examines the actualisation of the GROW model-based coaching process in enhancing the creativity of Islamic Education teachers at Madrasah Ibtidaiyah in Wlingi Subdistrict and the supporting and inhibiting factors. This study uses a qualitative descriptive approach with a case study type. Data were collected through participatory observation, in-depth interviews, and documentation studies. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing, with data validity checks using triangulation techniques (techniques and sources) and persistent observation to ensure the credibility and transferability of the findings. The results of the study indicate that the actualisation of coaching based on the GROW model (Goal, Reality, Options, Will) has been effective in enhancing the creativity of PAI teachers. The Goal stage is realised through the setting of specific and contextual objectives, Reality through the analysis of education reports and reflection on actual conditions, Options through the exploration of various innovative solutions and good practices, and Will through commitment to action, supervision, and evaluation. The main supporting factors include the commitment of supervisors and school principals, the availability of time and consistent schedules, and positive and communicative relationships.